Impact of motor self-efficacy on cyberbullying in adolescents and pre-adolescents in physical education - Rojo-Ramos, Jorge; Castillo-Paredes, Antonio; Mayordomo-Pinilla, Noelia; Galán-Arroyo, Carmen (Frontiers in Psychology, 2024)
In recent years, cyberbullying rates have increased, particularly in school environments. Cyberbullying is defined as repeated and malicious actions towards a subject via the Internet, with fatal consequences for the victim. The scientific literature has studied the factors that influence this type of behavior, finding that BMI is one of the main factors. On the other hand, hours and access to technologies, as well as physical activity, are other factors to consider. In this study, correlations between motor self-efficacy and cyberbullying were sought, considering that physical activity acts as a regulator in these cases. Significant inverse correlations were obtained between the ECIP-Q and E-AEM in the variables of gender, educational stage, daily PA, BMI, telephone ownership and hours spent on the Internet. There was an inverse correlation between motor self-efficacy and cyberbullying, where the higher the self-efficacy, the lower the abuse and victimization.In recent years, cyberbullying rates have increased, especially among adolescents in the school environment. According to the literature, the factors that influence this type of behaviour are access to technologies, physical activity and BMI, among others. The aim is to find correlations between motor self-efficacy and cyberbullying. The ECIP-Q and E-AEM questionnaire was applied to 1232 students from Spanish schools and institutes (8-18 years old) in a cross-sectional study. Significant inverse correlations were found between the ECIP-Q and the E-AEM on the variables of gender, educational stage, daily physical activity, BMI, telephone ownership and hours spent on the Internet. In conclusion, it can be understood that the higher the level of self-efficacy, the lower the level of abuse and victimisation. Therefore, physical activity could be considered to act as a regulator of cyberbullying. And it would be interesting for public administrations to increase the number of hours of physical education, to expand out-of-school physical activities and to promote an active lifestyle in order to eradicate this type of abusive school behaviour.